A family with normal sperm motility carrying a sY86 deletion in AZFa region and partial deletion in AZFc region - Zhao, Yuhong; Zhi, Weiwei; Xiong, Dongsheng; Li, Ningjing; Du, Xinrong; Zeng, Jiuzhi; Zhang, Guohui; Liu, Weixin (Frontiers in Genetics, 2025)
IntroductionUsually, patients with sY84 or sY86 deficiency present with azoospermia, but recent studies have shown that some males with partial AZFa deletions, including sY84 or sY86, exhibit normal fertility. Here, we reported a rare case of AZF deletion in a family, where both father and son exhibited a deletion at the sY86 site in the AZFa region and a partial deletion in the AZFc region.Methods and ResultsDetection was performed using classical multiplex polymerase chain reaction and the “Male AZF Full-region Detection” Panel, revealing specific deletions in AZFa: Yq11.21 (14,607,372–14,637,973), 30.6 kb; AZFc: Yq11.223–11.23 (25,848,831–27,120,665), 1.3 M for the father; and Yq11.223–11.23 (25,505,378–27,120,665), 1.6 M for the son. Notably, although the son’s sperm motility parameters showed no significant abnormalities, there was a history of failed pregnancies for twice, with sperm exhibiting a high rate of head defect.DiscussionGiven the complexities of the reproductive phenotype following AZF region deletions, additional extended genetic testing is necessary when partial deletions in the AZF region are detected, thus providing more accurate predictions of the spermatogenesis in patient. This study provides valuable insights and guidance for clinical decision-making and the implementation of assisted reproductive technologies in such cases.